1998
DOI: 10.1046/j.1460-9568.1998.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of a novel member of the fibroblast growth factor family

Abstract: A new member of the fibroblast growth factor (FGF) family, FGF-13, has been molecularly cloned as a result of high throughput sequencing of a human ovarian cancer cell library. The open reading frame of the novel human gene (1419 bp) encodes for a protein of 216 a.a. with a molecular weight of 22 kDa. The FGF-13 sequence contains an amino-terminal hydrophobic region of 23 a.a. characteristic of a signal secretion sequence. FGF-13 is most homologous, 70% similarity at the amino acid level, to FGF-8. Northern hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 52 publications
(113 reference statements)
1
18
0
Order By: Relevance
“…Which ligand(s) might activate FGFR3c and FGFR4 in follicles remains to be clarified. FGF-1, -2, -4, -8, -9 and -13 efficiently activate FGFR3c and -4 (Ornitz et al 1996, Greene et al 1998. In cattle, Fgf1 and Fgf2 expression was predominantly localized to theca cells (Berisha et al 2004), and Fgf2 expression increased with estradiol content (Berisha et al 2004) as did the expression of Fgfr3c in granulosa cells in the present study.…”
Section: Fgfr3csupporting
confidence: 61%
“…Which ligand(s) might activate FGFR3c and FGFR4 in follicles remains to be clarified. FGF-1, -2, -4, -8, -9 and -13 efficiently activate FGFR3c and -4 (Ornitz et al 1996, Greene et al 1998. In cattle, Fgf1 and Fgf2 expression was predominantly localized to theca cells (Berisha et al 2004), and Fgf2 expression increased with estradiol content (Berisha et al 2004) as did the expression of Fgfr3c in granulosa cells in the present study.…”
Section: Fgfr3csupporting
confidence: 61%
“…The growth factor is likely to be mitogenic for the melanoma cells because it stimulates the mitogen-activated protein kinase pathway (Ref. 77 …”
Section: Discussionmentioning
confidence: 99%
“…Frame-shift mutation in the exon 4 of FGF14 gene and DNA polymorphisms is found in patients with inherited ataxias [19].…”
Section: Expression Of Intracellular Fgfs In the Nervous Systemmentioning
confidence: 99%
“…Early studies showed that FGF13 could induce tyrosine phosphorylation of mitogen-activated protein kinase (MAPK) and phospholipase C-gamma (PLC-γ) in hippocampal astrocytes [19]. Treatment of neuronal cultures from rat embryonic cortex with FGF13 increased the number of neurons containing gamma-aminobutyric acid (GABA) and choline acetyltransferase enzymes [19].…”
Section: Fgf1functions In Neural Developmentmentioning
confidence: 99%